Epidemiological study of secondary bloodstream infections: The forgotten issue - Laura Sante; Armando Aguirre-Jaime; Maria Antonia Miguel; María José Ramos; Yanet Pedroso; María Lecuona (Elsevier, 2019)
Objective: Secondary bacteraemia infections (SBI) are poorly studied. We analyse the epidemiology of nosocomial SBI, potential risk factors and mortality of affected patients. Methods: Prospective study of patients with bacteraemia from 2009 to 2014 in a tertiary hospital. For each SBI was recorded: primary source of infection, aetiological agent, demographic data, intrinsic and extrinsic risk factors and mortality during the episode. Results: 429/1918 episodes of Nosocomial Bacteraemia (NB) (22%) were SBI (average Incidence Density: 0.41% days of admission). Onco-hematological services had the highest Incidence Density of SBI. Surgical Site Infection-SBI (SSI-BSI) was the most frequent SBI (27%), followed by Urinary Tract Infection-SBI (UTI-BSI) (24%). Gram-negative bacteria were the most prevalent microorganism (61.1%). The median interval between SBI episodes to discharge was 37 ± 59days. Mortality rate was 29%. These patients had many intrinsic and extrinsic risk factors such as urinary catheterization (68%), CVC (69%), Arterial hypertension (48%) and hospitalization in the six previous months (45%).Mean age was significantly higher in patients with UTI-BSI and SSI-BSI. Average stay from admission to the development of bacteraemia was statistically lower in patients with Intra-abdominal Infection bacteraemia (IAB-BSI). Patient with SSI-BSI had oncologic processes and had undergone for more Mechanical ventilation than UTI-SSBI and Respiratory Tract Infections Bacteraemia (RTI-BSI). The use of CVC was significantly higher in RTI-BSI. Conclusions: SBI accounts for almost a quarter of all NB. Patients has multiple comorbidities, increases hospital stay and mortality. It would be necessary to establish measures to rapidly diagnose and treat the primary infection, in order to prevent the onset of SBI. Keywords: Bloodstream infection, Nosocomial bacteraemia, Secondary bacteraemia infections, Epidemiology, Infection control